Pengaruh Kegiatan Musyawarah Guru Mata Pelajaran (MGMP) Terhadap Pengembangan Kompetensi Profesional Guru Bahasa Indonesia - Uray Ferry Haryanto (CENDEKIA: Jurnal Ilmu Sosial, Bahasa dan Pendidikan, 2023)
This research aims to ; 1) To find out how the Subject Teacher Deliberation Activities (MGMP) are conducted; 2) To find out what the professional competence of Indonesian language teachers at Tanjung Pinang City Middle School is. 3) To determine the influence of Subject Teacher Deliberation Activities (MGMP) on the professional competence of Indonesian Language teachers in Tanjung Pinang City Middle Schools. The research subjects were 45 Indonesian Language Teachers at Tanjung Pinang City Middle Schools. Data collection techniques using observation and documentation questionnaires. The research results show that Subject Teacher Deliberation Activities (MGMP) activities reached 87%. This is proven by the results of the questionnaire data which reached 87%, which is in the range of 81-100% in the Very Good category. Meanwhile, research results on teacher professional competence reached 86%, this is proven by the results of questionnaire data which reached 86%, which is in the range of 81-100% in the Very Good category. The influence of Subject Teacher Deliberation Activities (MGMP) on the professional competence of Indonesian Language teachers in Tanjung Pinang City Middle School. The calculation results obtained a value of rxy = 0.838 which is between (0.800 - 1.000). Thus, rcount is greater than rtable at the 5% significance level and 1% significance level (0.294 < 0.380 < 0.838), this means that Ha is accepted and Ho is rejected. So the correlation analysis value shows that the influence of Subject Teacher Deliberation Activities (MGMP) on the professional competence of Indonesian Language teachers in Tanjung Pinang City Middle Schools is 70.2%.